2002
DOI: 10.3109/s101650200019
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines and chemokine receptors in the pathogenesis of systemic sclerosis

Abstract: Activation of the immune system and increased synthesis of extracellular matrix proteins by fibroblasts are hallmarks in the pathogenesis of systemic sclerosis (SSc). The mechanisms that initiate the accumulation of inflammatory cells are still unknown. Chemokines are a family of small molecules that are divided into subfamilies according to the position of NH2-terminal cysteine motif. A new nomenclature for chemokines recently has been introduced in an attempt to overcome the confusion resulting from a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Recent studies have shown how vast and ever-expanding the field of biomarkers is in SSc. Biomarkers will become increasingly important in research and, consequently, in the diagnosis and therapeutic approach to SSc [30][31][32][33][34][35][36][59][60][61][62][63][64][65][66][67]. Several studies have demonstrated the involvement of at least 240 pathways and numerous dysregulated proteins in the pathogenesis of SSc, so the field of biomarkers in this disease is complex and evolving [30][31][32][33][34][35][36][59][60][61][62][63][64][65][66][67].…”
Section: Biomarkers In Systemic Sclerosismentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown how vast and ever-expanding the field of biomarkers is in SSc. Biomarkers will become increasingly important in research and, consequently, in the diagnosis and therapeutic approach to SSc [30][31][32][33][34][35][36][59][60][61][62][63][64][65][66][67]. Several studies have demonstrated the involvement of at least 240 pathways and numerous dysregulated proteins in the pathogenesis of SSc, so the field of biomarkers in this disease is complex and evolving [30][31][32][33][34][35][36][59][60][61][62][63][64][65][66][67].…”
Section: Biomarkers In Systemic Sclerosismentioning
confidence: 99%
“…Biomarkers will become increasingly important in research and, consequently, in the diagnosis and therapeutic approach to SSc [30][31][32][33][34][35][36][59][60][61][62][63][64][65][66][67]. Several studies have demonstrated the involvement of at least 240 pathways and numerous dysregulated proteins in the pathogenesis of SSc, so the field of biomarkers in this disease is complex and evolving [30][31][32][33][34][35][36][59][60][61][62][63][64][65][66][67]. Cytokeratin 17 (CK17), marginal zone protein B1 (MZB1), and leucine-rich α2-glycoprotein-1 (LRG1) appear to be potential biomarkers for SSc, with CK17 negatively associated with disease severity and higher values of CK17 protective [37,[59][60][61][62][63][64][65][66][67].…”
Section: Biomarkers In Systemic Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Given their critical role in immune cell function, it is hardly surprising that chemokines appear important for the development and propagation of autoimmune diseases; and may represent useful biomarkers for disease evolution. In SSc, it was early shown that the CC chemokine 2 (CCL2) was important for the development of tissue fibrosis (7). More recently, studies indicate biomarker potential of additional chemokines including CCL18, CX3CL1 and CXCL4 in SScassociated interstitial lung disease (5,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Eine wichtige Rolle könnten dabei Chemokine spielen. Bei Chemokinen handelt es sich um eine Familie kleiner Proteine, welche die Migration von Leukozyten im Rahmen eines Entzündungsgeschehens steuern[51]. Etliche Chemokine weisen in der SSc ein abnormes Expressionsmuster auf.…”
unclassified